Disciplinary offense as the basis for termination of labor relations at the initiative of the employer - Babenko, Eduard (Київський національний університет імені Тараса Шевченка, 2018)
The article systemically considers disciplinary misconducts as a reason for terminating the employer-employee relations on the employer’s initiative. The related norms of labour legislation have been analyzed. On this basis a general conclusion is drawn according to the necessity to comply with the terms and procedures determined by law, as well as to provide the obligatory evidences of a disciplinary misconduct fact.

У статті систематизовано розглянуто дисциплінарний проступок як підставу припинення трудових правовідносин з ініціативи роботодавця. Проаналізовано відповідні норми трудового законодавства. Зроблено узагальнюючий висновок про необхідність дотримання визначенихзаконодавством строків та порядку, а також обов’язкового доведення факту вчинення дисциплінарного проступку.
ДИСЦИПЛІНАРНИЙ ПРОСТУПОК ЯК ПІДСТАВА ПРИПИНЕННЯ ТРУДОВИХ ПРАВОВІДНОСИН З ІНІЦІАТИВИ РОБОТОДАВЦЯ
Keywords: disciplinary misconduct; reasons; terminating the employer-employee relations; protection of labour rights; дисциплінарний проступок; підстави; припинення трудових правовідносин; захист трудових прав